How mental health care should change as a consequence of the COVID-19 pandemic. (September 2020) - Moreno, Carmen; Wykes, Til; Galderisi, Silvana; Nordentoft, Merete; Crossley, Nicolas; Jones, Nev; Cannon, Mary; Correll, Christoph U; Byrne, Louise; Carr, Sarah; Chen, Eric Y H; Gorwood, Philip; et al.
Summary: The unpredictability and uncertainty of the COVID-19 pandemic; the associated lockdowns, physical distancing, and other containment strategies; and the resulting economic breakdown could increase the risk of mental health problems and exacerbate health inequalities. Preliminary findings suggest adverse mental health effects in previously healthy people and especially in people with pre-existing mental health disorders. Despite the heterogeneity of worldwide health systems, efforts have been made to adapt the delivery of mental health care to the demands of COVID-19. Mental health concerns have been addressed via the public mental health response and by adapting mental health services, mostly focusing on infection control, modifying access to diagnosis and treatment, ensuring continuity of care for mental health service users, and paying attention to new cases of mental ill health and populations at high risk of mental health problems. Sustainable adaptations of delivery systems for mental health care should be developed by experts, clinicians, and service users, and should be specifically designed to mitigate disparities in health-care provision. Thorough and continuous assessment of health and service-use outcomes in mental health clinical practice will be crucial for defining which practices should be further developed and which discontinued. For this Position Paper, an international group of clinicians, mental health experts, and users of mental health services has come together to reflect on the challenges for mental health that COVID-19 poses. The interconnectedness of the world made society vulnerable to this infection, but it also provides the infrastructure to address previous system failings by disseminating good practices that can result in sustained, efficient, and equitable delivery of mental health-care delivery. Thus, the COVID-19 pandemic could be an opportunity to improve mental health services.